Cosmotechnical Difference in Architecture and Urbanism - Dulmini Perera; Samuel Koh (Footprint)
This issue of Footprint explores the intersection between architecture, technology and cosmology. It does so by examining the concept of ‘cosmotechnics’, as proposed by the philosopher Yuk Hui. Cosmotechnics – defined as ‘the unification of the cosmic and moral order through technical activities’ – proposes that technology is not a universal category but always exists in a co-productive relationship with a specific cosmology. While cosmotechnics has fomented new scholarship in philosophy, STS and cultural theory, its implications for architecture remain underexplored. Here, we introduce the concept of cosmotechnics, distinguish it from previous approaches to technology and cosmology, and outline its unique relevance to architectural discourse. In doing so, we present a core theme of the issue: technologies, cosmologies and architectures do not only influence one another, but are indeed inseparable, mutually Introduction Cosmotechnical Difference in Architecture and Urbanism Dulmini Perera and Samuel Koh, editors Bauhaus-Universität Weimar, Germany constitutive, and conjoined in continual coevolution. Finally, we introduce the contributions that comprise the issue – a diverse set of explorations of the theoretical and practical intersections between cosmotechnics and architecture.